1656. Factors associated with low TB preventative therapy prescription rates among healthcare workers in rural South Africa. (31st December 2020) - Ahmed, Amiya A; Grammatico, Megan A; Malinga, Sipho; Makhunga, Philile; Moll, Anthony; Ladines-Lim, Joseph B; Jones, Justin; Choi, Koeun; Shenoi, Sheela
Abstract: Background: Despite South Africa's initial successful rollout of tuberculosis preventative therapy (TPT) to reduce tuberculosis (TB) incidence among HIV-infected patients, recent data suggest prescription rates have decreased. This study aimed to identify associations with low prescription rates among healthcare workers (HCWs) in rural South Africa. Methods: A cross-sectional survey was administered Nov-Dec 2019 to HCWs at a 350 bed rural district hospital and 14 primary care clinics (PCCs) in the Msinga sub-district, South Africa to obtain self-reported data on prescription rates as well as knowledge, attitudes, practices, and beliefs regarding isoniazid preventive therapy, the current TPT regimen. HCWs included professional nurses, staff nurses, counselors, and medical officers. Survey questions were consolidated into scores using exploratory factor analysis. Univariate and multivariate associations with low prescription rates, defined as < 50% of eligible patients, were determined for prescribers. Results: Among 160 participants, the median ( + IQR) age was 39 (+13) years, 76% were women, 78% worked at a PCC, and 35% were prescribers, including professional nurses (82%) and medical officers (19%). The median ( + IQR) years as a HCW and managing patients living with HIV (PLH) among prescribers was 14 ( + 15.5) and 10 ( + 11.5) years, respectively. Compared to prescribers, non-prescribers reported more stigma (71% v. 54%; p=0.04) and placed less priority on prevention compared to treatment (32% v. 58%; p< 0.01). Among prescribers (n=54), univariate analysis identified that patient nondisclosure (OR 4.17 95% CI 1.23-14.14; p=0.02) was associated with low TPT prescription rates. Poor self-reported knowledge also trended towards significance (OR 5.23 95% CI 0.85-32.08; p=0.07). After multivariate analysis, only perceived patient nondisclosure was significantly associated with low prescription TPT rates (aOR 4.17 95% CI 1.23-14.14; p=0.02). Conclusion: HCWs who believed their patients had not disclosed that they were taking TPT were significantly less likely to prescribe it to their patients. Strengthening HCW training about indications for and mortality benefit of TPT as well as stigma reduction is critical to enhancing TPT implementation. Disclosures: All Authors : No reported disclosures